Evaluation in Small Development Non-Profits - Kelly, Leanne M. author. aut Link
XVII, 215 p. 6 illus., 2 illus. in color.
Keywords: ‘Does size matter? As a first, this volume explains why the scale of a development NGO should determine how it goes about gathering, analysing and applying information to learn about and improve its efforts. It convincingly demonstrates why monitoring and evaluation systems of big NGOs are simply inappropriate for the, by far larger, number of their smaller counterparts. For the NGO majority, before turning to canons in the field, start with this book.’ –Alan Fowler, Co-founder of the International NGO Training and Research Centre (INTRAC), Oxford, UK ‘Leanne Kelly's new book provides a very timely and original insight into the relatively understudied area of evaluation in small NGOs. In particular, her exploration of the disjuncture between methodological rigour and the degree to which evaluation findings are actually used, raises important questions about what we mean by ‘quality’ in the evaluation field. An important read for both evaluators, practitioners and funding agencies.’ –Chris Roche, Professor of Development Practice, La Trobe University, Melbourne, Australia Research on evaluation shows that low-use and non-use of evaluation is common, yet evaluation is hailed as beneficial and worthwhile. The worth of evaluation is tied to its utilisation, presenting a paradox if evaluation is both revered and underutilised. This book investigates this paradox in the under-researched context of small development non-profit organisations, which have specific resource constraints and ‘bottom up’ community development values that complicate their ability to do and use evaluation in line with top down directives. The book examines the utility, meaningfulness, and purpose of evaluation from small non-profit perspectives, and explores whether evaluation has value for these organisations. For development practice, it presents evaluative alternatives that reconceptualise evaluation as part of the active process of development rather than as an interval-based add-on. For evaluation theory, it highlights a historical preoccupation with improving evaluation without assessing its inherent worth, and considers alternative ways to enhance the value of evaluation for small non-profits. Leanne M. Kelly has spent most of the past two decades working in social services and community development not-for-profits across four continents. She has worked for small, medium, and large not-for-profits with the majority of her roles focused on evaluation.